Serum Ferritin Correlates With Liver Fat in Male Adolescents With Obesity - Mörwald, Katharina; Aigner, Elmar; Bergsten, Peter; Brunner, Susanne M.; Forslund, Anders; Kullberg, Joel; Ahlström, Hakan; Manell, Hannes; Roomp, Kirsten; Schütz, Sebastian; Zsoldos, Fanni; Renner, Wilfried; et al. (Frontiers in Endocrinology, 2020)
Non-alcoholic fatty liver disease (NAFLD) contributes essentially to the burden of obesity and starts in childhood. NAFLD can progress to cirrhosis and hepatocellular carcinoma. The early phase of NAFLD is crucial because during this time the disease is fully reversible. Pediatric NAFLD shows unique features of histology and pathophysiology compared to adults. Changes in serum iron parameters are common in adult NAFLD and have been termed dysmetabolic iron overload syndrome characterized by increased serum ferritin levels and normal transferrin saturation; however, the associations of serum ferritin, inflammation and liver fat content have been incompletely investigated in children. As magnetic resonance imaging (MRI) is an excellent measure for the degree of liver steatosis, we applied this method herein to clarify the interaction between ferritin and fatty liver in male adolescents. 150 male pediatric patients with overweight and obesity were included. We studied a subgroup of 62 male patients with and without NAFLD in whom we determined liver fat content, visceral adipose tissue and subcutaneous adipose tissue extent with a 1.5T MRI (Philips NL). All patients underwent a standardized oral glucose tolerance test. We measured uric acid, triglycerides, HDL-, LDL-, total cholesterol, liver transaminases, high sensitive CRP (hsCRP), interleukin-6, HbA1c, and insulin. In univariate analysis, ferritin was associated with MRI liver fat, visceral adipose tissue content, hsCRP, AST, ALT and GGT, while transferrin and soluble transferrin receptor were not associated with ferritin. Multivariate analysis identified hsCRP and liver fat content as independent predictors of serum ferritin in the pediatric male patients. Our data indicate that serum ferritin in obese male subjects is mainly determined by liver fat content and inflammation but not body iron status.